Emergency Distribution Network Design & Analysis for Consecrated COVID 19 Hospital Zone - Rahman, Md. Lutfur; Shatil , Md. Abu Hena (AIUB Journal of Science and Engineering (AJSE), 2022)
A power distribution network is always a key topic in a grid system because of more complexity. Rapidly or sudden load increasing to a particular one or two feeders can arise uncertainty and unbalance conditions in the system. Voltage fluctuations, Deviations, THD (total harmonic distortion), Reactive power imbalances can seriously unstable the grid for load increasing situations. In recent days due to COVID 19 condition, dedicated hospitals are connected to the distribution network. Because of its urgency and usefulness, a new type of distribution network called loop plus parallel has been presented in this paper. Finally, the simulation studies show better performance when comparing the traditional types of networks. New distribution network shows promising values in THD, Voltage deviation and also for reactive power imbalance.